Technological trends in 2010 - Serrano-Cobos, Jorge (Anuario ThinkEPI, 2011)
In 2010 technology trends became popular that were as diverse and innovative as net neutrality, internet television, video on demand, mobile commerce (due to the increase of the smartphone market), new algorithms that try to compete with Google, content spam, augmented reality, progress on ebooks and transmedia, multitouch interaction, digital out-of-home (dooh) advertising or digital signage, and open data web (open data and linked data) that replaces the semantic web, while the popularization of web 2.0 leads to intensive use of social networks in all areas of digital life, including social commerce.